Guided Discovery Approach in the Development of Calculus Modules on Derivative Material with Islamic Nuance and Environmental Insight. (February 2020) - Supriadi, N; Diana, N; Muhassin, M; Farida; Lestari, B D
Abstract: The development of teaching materials in the form of modules needs to be developed in calculus courses to help students understand derivative materials. This development research aims to determine the development and feasibility of the developed module, namely the calculus modules on derivative material with Islamic nuance and environmental insight. The method used in this research is Research and Development (R&D) using the 4D model proposed by Thiagajaran. The steps taken are to Define, Design, Development, and Disseminate. Based on the results of the research, the results of the validation by the material experts, media experts, and Islamic religious and environment experts are deemed valid. Based on small-scale testing on the product's attractiveness, the module is declared as very attractive. Thus, based on the assessment of validators and small-scale trials, the developed module is declared as feasible.